2011
DOI: 10.1525/mp.2012.29.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Who Enjoys Listening to Sad Music and Why?

Abstract: although people generally avoid negative emotional experiences in general, they often enjoy sadness portrayed in music and other arts. The present study investigated what kinds of subjective emotional experiences are induced in listeners by sad music, and whether the tendency to enjoy sad music is associated with particular personality traits. One hundred forty-eight participants listened to 16 music excerpts and rated their emotional responses. As expected, sadness was the most salient emotion experienced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
262
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(312 citation statements)
references
References 21 publications
35
262
6
1
Order By: Relevance
“…One possible explanation could be that the nostalgia was a by-effect of the music-evoked sadness, rather than an effect of the music. It has been reported previously that one common trigger of nostalgia is negative affect such as sadness (Wildschut, Sedikides, Arndt, & Routledge, 2006), and these emotions have been hard to disentangle in previous studies (Vuoskoski et al, 2012).…”
Section: Problems and Future Directionsmentioning
confidence: 90%
“…One possible explanation could be that the nostalgia was a by-effect of the music-evoked sadness, rather than an effect of the music. It has been reported previously that one common trigger of nostalgia is negative affect such as sadness (Wildschut, Sedikides, Arndt, & Routledge, 2006), and these emotions have been hard to disentangle in previous studies (Vuoskoski et al, 2012).…”
Section: Problems and Future Directionsmentioning
confidence: 90%
“…The music can be both perceived and/or felt, wherein perceived emotion may be described as the emotion the listener judges the music to be trying to convey, and felt emotion is the emotion the listener actually experiences (Gabrielsson 2001). An example might be music with a "sad" flavour which, when played to a listener in a negative emotional state may actually make the listener feel happier (Vuoskoski et al 2012). Participants in our experiments were carefully instructed, via written and oral explanations, to report their felt emotions as they completed the experiment.…”
Section: Overviewmentioning
confidence: 99%
“…physiological reactions to music (Miu & Balteş, 2012), but Vuoskoski and colleagues have shown that empathy is associated with susceptibility to induced sadness from music , and also enjoyment of sad music (Vuoskoski, Thompson, McIlwain, & Eerola, 2012). Researchers have also suggested that music increases prosocial behavior in children (Kirschner & Tomasello, 2010), adolescence (Rickson & Watson, 2003) and adults (Greitemeyer, 2009).…”
mentioning
confidence: 99%